2014
DOI: 10.2169/internalmedicine.53.2687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Hemoperfusion with Polymyxin B-immobilized Fiber on Rapidly Progressive Interstitial Lung Diseases

Abstract: Objective Direct hemoperfusion with polymyxin B-immobilized fiber columns (PMX-DHP) has been used for the treatment of septic shock. It was recently suggested that PMX-DHP may also be effective in acute exacerbations of idiopathic pulmonary fibrosis (IPF). However, all previous reports are case series without controls. The aim of the study was to determine the effects of PMX-DHP on the prognosis of the patients with rapidly progressive interstitial lung diseases (ILDs) in a case-control setting. Methods We her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 25 publications
5
36
1
Order By: Relevance
“…While we found no significant difference in the overall survival proportion between our ILD patients with and without PMX‐DHP treatment, the patients treated with PMX‐DHP within 3 days of AE onset showed better prognosis. This result was compatible with a previous report demonstrating a better prognosis in patients undergoing PMX‐DHP on the first day with steroid pulse therapy compared with patients treated with immunosuppressant alone …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While we found no significant difference in the overall survival proportion between our ILD patients with and without PMX‐DHP treatment, the patients treated with PMX‐DHP within 3 days of AE onset showed better prognosis. This result was compatible with a previous report demonstrating a better prognosis in patients undergoing PMX‐DHP on the first day with steroid pulse therapy compared with patients treated with immunosuppressant alone …”
Section: Discussionsupporting
confidence: 93%
“…PMX‐DHP was originally invented as a method to remove endotoxins and improve the haemodynamics and P/F ratio in patients with septic shock by adsorbing the circulating endotoxins in blood via direct extracorporeal hemoperfusion without exerting toxicity . Recent studies have suggested that PMX‐DHP may improve the prognosis of patients with AE‐IPF or dermatomyositis . Most of these studies report that PMX‐DHP improves oxygenation and decreases white blood cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches are typically followed by a rapid taper and cessation of prednisone within several weeks, based on the rationale that chronic prednisone use is likely harmful in IPF [9]. Several other investigational agents have been studied in AE-IPF including polymyxin B-immobilised fibre cartridge [61][62][63][64], tacrolimus [65] and cyclosporine [66][67][68]; however, there are currently insufficient data to support the routine use of these medications.…”
Section: Managementmentioning
confidence: 99%
“…Decreased levels of not only endotoxin, but also various mediators including IL‐6, IL‐8, IL‐10, tumor necrosis factor‐α, and interferon‐γ are reported in patients treated with PMX‐DHP . PMX‐DHP was first developed in Japan in the early 1990s with the aim of removing circulating endotoxin, and is becoming established for the treatment of adult sepsis and is suggested to improve oxygenation in patients with various lung diseases . In this study, 2 h CHDF was added to the latter half of 4 h PMX‐DHP in the active treatment group.…”
Section: Discussionmentioning
confidence: 99%